The Impact of Land Transfer on Farmers' Happiness: The Mediating Effect of Social Aspects - Zhang, Weiwei; Zhou, Qiuxiang; Li, Wei; Nupueng, Somjai (Ital Publication, 2025)
This study investigated the mechanism through which land transfer impacts farmers' happiness in China, focusing on the mediating roles of household income and social equity, and the moderating effect of social capital. Utilizing convenience sampling through WJX platform, 431 farmers in Guangxi (2024) were selected as samples, and conducted structural equation modeling with Smart-PLS 4.0. Key findings reveal: (1) Land transfer exerts a significant positive effect on farmers' happiness; (2) Household income and social equity mediate 69.63% of this effect, with social equity demonstrating stronger mediation; (3) Social capital amplifies the equity pathway while showing nonsignificant moderation on income effects. Methodologically, this study applied multi-mediation moderated SEM in farmers' happiness studies, integrating both economic and psychosocial dimensions. Theoretically, these results challenge conventional income-centric paradigms by establishing social equity as the dominant mechanism, revealing that policy effectiveness in land reforms depends more on equity perceptions than absolute income gains. They provide empirical support for the application of social capital theory and social equity theory in rural land issue studies, highlighting critical factors that should be considered in policy formulation, and provide valuable empirical evidence for the government and policymakers, aiding in the optimization of land transfer policies to enhance farmers' happiness.